THE INFLUENCE OF INDICATORS OF ATMOSPHERIC AIR POLLUTION ON THE HEALTH OF THE POPULATION - Abdukadirova Lola Kabulovna (Modern American Journals, 2025)
The article examines the composition of the atmospheric air of two selected districts of the city of Tashkent, as well as comparatively compared indicators of morbidity of the population living in this area.
Keywords: Atmosphere, ecology, environment, dosage, morbidity of children, public health.